OPTN/SRTR 2019 Annual Data Report: Pancreas. Issue 2 (17th February 2021) - Kandaswamy, R.; Stock, P. G.; Miller, J.; Skeans, M. A.; White, J.; Wainright, J.; Kyaw, N. T. T.; Niederhaus, S.; Israni, A. K.; Snyder, J. J.
Abstract: The overall number of pancreas transplants decreased slightly, from 1027 in 2018 to 1015, in 2019, up from a nadir of 947 in 2015. However, the number of simultaneous pancreas‐kidney transplants (SPKs) increased in 2019, with a corresponding drop in pancreas‐after‐kidney transplants (PAKs) and pancreas transplants alone (PTAs). New waitlist registrations increased to 1772 in 2019, from 1606 in 2018. This was predominately driven by SPK listings, and those with type 2 diabetes. Waiting time for SPK decreased by 2 months, to a median of 12 months in 2019, but PTA recipient mean waiting time remained substantially higher, at 24 months, in 2018. Both short‐ and long‐term outcomes, including patient survival, kidney graft survival, and acute rejection‐free graft survival, have shown consistent improvement over the last decade. Pancreas graft survival data with the uniform definition of allograft failure is being collected by the Organ Procurement and Transplant Network (OPTN) and will be included in a future report.